Analisis Pengaruh Inklusi Perbankan Syariah terhadap Pembiayaan UMKM Sektor Halal di Indonesia - Muhammad Khozin Ahyar (Al-Tijary, 2019)
Financial inclusion is an issue that is being echoed by the government together with other authorities and stakeholders. One of the main targets of financial inclusion besides households is the MSMEs. Some indicators of financial inclusion, namely access, use and quality. This study aims to analyze how the influence of Islamic banking inclusion (BUS and UUS) from access indicators to the distribution of MSME financing. The access indicator used is the number of Islamic banking offices which include KP, KC, KCP and KK. This research uses a quantitative method with a VAR (Vector Autoregression) model. The results showed that the number of BUS and UUS offices affect MSMEs in Islamic banking financing. In addition, Islamic banking in Indonesia is still not optimal in channeling financing to MSMEs. Various ways can be done by Islamic banking in order to expand access to MSME actors, including developing the Financial Technology (Fintech) system, expanding Islamic banking agents through the Laku Pandai program and expanding cooperation with MSME stakeholders.